'Hands up technique': An alternative surgical setup for Brachioplasty. (September 2019) - Appukuttan, A.; Chukwulobelu, R.; Ragoowansi, R.
Summary: For routine brachioplasty, conventional intra-operative positioning involves abducted arms resting on two tables with the patient supine. This technique does not facilitate intra-operative comparison for symmetry and engages one assistant to hold the arm at all times. We describe a novel positioning technique for brachioplasty using Chinese finger traps and drip stands which is safe, easy to reproduce, obviates the need for a positioning assistant and facilitates symmetrical resection.